Comparison of functional dorsal attention network alterations in breast cancer survivors before and after chemotherapy. Issue 33 (20th August 2021) - Shen, Chao-Yu; Tsai, Yuan-Hsiung; Chen, Vincent Chin-Hung; Chou, Ming-Chih; McIntyre, Roger S.; Weng, Jun-Cheng
Abstract : Abstract: Breast cancer is the leading type of cancer among women worldwide, and a high number of breast cancer patients are suffering from psychological and cognitive disorders. This cross-sectional study used resting-state functional magnetic resonance imaging (rs-fMRI) and clinical neuropsychological tests to evaluate the possible underlying mechanisms. We enrolled 32 breast cancer patients without chemotherapy (BC), 32 breast cancer patients within 6 to 12 months after the completion of chemotherapy (BC_CTx) and 46 healthy controls. Participants underwent neuropsychological tests and rs-fMRI with mean fractional amplitude of low-frequency fluctuation and mean regional homogeneity analyses. Between groups whole-brain voxel-wise rs-fMRI comparisons were calculated using two-sample t test. rs-fMRI and neuropsychological tests correlation analyses were calculated using multiple regression. Age and years of education were used as covariates. A false discovery rate-corrected P -value of less than .05 was considered statistically significant. We found significantly alteration of mean fractional amplitude of low-frequency fluctuation and mean regional homogeneity in the frontoparietal lobe and occipital lobe in the BC group compared with the other 2 groups, indicating alteration of functional dorsal attention network (DAN). Furthermore, we found the DAN alteration was correlated with neuropsychological impairment. The majority of potential underlying mechanisms of DAN alteration in BC patients may due to insufficient frontoparietal lobe neural activity to drive DAN and may be related to the effects of neuropsychological distress. Further longitudinal studies with comprehensive images and neuropsychological tests correlations are recommended.